Design of split-capacitors applied in positive output super-lift luo-converters - Lee, Hansel. (2012)
Voltage Lift Technique has been successfully employed in design of DC/DC converters because it overcomes the effects of parasitic elements effectively. By employing Super Lift Technique, a more advance technique compared to voltage lift technique, it is possible to further enhance its output voltage. This technique has the most significant contribution in Power Electronics, e.g. four series Super-Lift Converters.